Integration of Local Wisdom in Nonfiction Reading Instruction: A Theoretical Review through Barrett's Taxonomy of Reading Comprehension - Eka Wahyuni, Mulva Dessy; Subrata, Heru; Hendratno (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2026)
This study examines the integration of local wisdom-based instructional materials in nonfiction reading comprehension for elementary school students using Barrett’s Taxonomy as a theoretical framework. A systematic literature review was conducted on 20 empirical studies published between 2021 and 2025 that explore culturally responsive teaching materials in reading instruction, focusing on their development, implementation, and effectiveness in enhancing comprehension skills. The findings indicate that local wisdom-based materials consistently improve students’ literal, inferential, and evaluative comprehension, while also strengthening cultural identity, motivation, and engagement by connecting learning content to students’ real-life cultural contexts. Barrett’s Taxonomy supports this process by providing a structured progression from basic understanding to higher-order critical thinking, making reading instruction more systematic and meaningful. However, most existing studies still emphasize narrative texts and show limited explicit application of Barrett’s Taxonomy in nonfiction contexts, indicating a significant research gap. Additionally, variations in implementation and limited contextual diversity suggest the need for broader investigation. In conclusion, the integration of local wisdom-based materials with Barrett’s Taxonomy is an effective approach to enhancing nonfiction reading comprehension in elementary education, as it combines cultural relevance with structured cognitive development. Nevertheless, further research is needed to expand its application across different text types, improve instructional design models, and examine its long-term impact on students’ comprehension abilities and cultural understanding.